Pengawasan Pemerintah Kota Banda Aceh dalam Penertiban Pengemis di Bawah Umur - Bobby Rahman; Rudi Kurniawan; Rizki Utami; Zamzami Zainuddin (Sekolah Tinggi Ilmu Administrasi Nasional, 2020)
This research discusses the proliferation of underage beggars in Banda Aceh, the capital of the Aceh province, Indonesia. This case confronts the local law, namely Qanun No. 11 of 2013 articles 45 and paragraphs 46. The focus of this study was to identify the effectiveness of direct and indirect monitoring and inspecting of underage beggars in this capital city, and at the same time to observe the obstacles encountered in handling this issue. A qualitative method was employed in collecting the data through observation, interviews, and documentation. The result of the investigation affirmed that the obstacle in overcoming beggars is the unavailability of social rehabilitation centers. Besides, beggars who are caught are only managed after they are released, then they repeat their actions because they are constrained by their daily needs. The patrol work carried out by the Office of Social Affairs often battled with resistance, such as when they rebelled and tried to escape in order to be caught by the officers. Most beggars in the capital city of Aceh are categorized as children and elderly people so that when conducting training, it is difficult to give punishment like to other beggars. Furthermore, the minimal budget provided by the government to curb beggars also becomes a challenge, especially to control underage beggars with routine patrols.